Study for the Assessment of Macrovascular Complications of Madhumeha (T2DM) and its Association with Sara (International Journal of Ayurveda and Pharma Research, 2023)
Diabetic complications are generally classified into macrovascular and microvascular conditions. Depending on the location of the atherosclerotic lesion, macrovascular disease (coronary artery disease, cerebrovascular disease, peripheral vascular disease) may occur. The prevalence of diabetes and its complication is increasing all over the world, particularly in developing countries. It has emerged as a major public health problem in our country. The disease Madhumeha is described under Prameha and it is the subtype of Vataja Prameha Madhumeha manifest due to morbidity of Shukra and Shonita which is incurable. In Madhumeha, Sara is the most useful entity for the measurement of strength and the life span of an individual, so it’s very important to know about Sara from a treatment point of view because lean and thin persons may have Pravara Sara. Here the attempt will be made to highlight the study for the assessment of the macrovascular complication of Madhumeha and its association with Sara. This study has been done on the basis of subjective and objective parameters in T2DM patients with macrovascular complications. Sara was assessed in each subject as per the scheduled proforma. In the research, we found that the diabetic complications were related to Sara, which is statistically highly significant. The conclusion of the study is Avara Meda Sara patients were found with all types of complications, only a few patients with complications belong to Madhyama Meda Sara, and there are no patients belonging to Pravara Meda Sara. Maximum patients of T2DM complication of Asthi, Majja and Shukra Sara having Madhyama Sara.